Influences of swimming test distance in the anaerobic threshold determination and blood lactate levels - Almeidal, A. G.; Gobatto, C. A.; Lenta, C.; Kokubun, E. (Medicine & Science in Sports & Exercise, 1999)
This study evaluated the proposal that blood lactate concentrations, which correspond to the anaerobic threshold (AT), can be universally established as 3.5 or 4.0 mM in 200 and 400-m swimming tests. Ss (M = 8; F = 6) performed two different protocols for determining (AT). In test 1, three 400-m swims at 85, 90, and 100% of maximal velocity for the distance were performed. AT was deemed as the swimming velocity that corresponded to 4 mM lactate concentration. In test 2, the same procedure was followed but 200-m distances were covered and 3.5 mM lactate concentration used. Maximal lactate concentrations were significantly higher for the 200-m test than the 400-m test. AT for 200 m was significantly higher than that for 400 m. The two tests were not equivalent. Implication: The determination of anaerobic threshold in swimming is dependent upon the criterion used to decide upon AT and the distance swum in the protocol. Consequently, AT in swimming is protocol and criterion dependent.